Influence of the support of copper catalysts on activity and 1,2-dichloroethane selectivity in ethylene oxychlorination - Zuzana Vajglová; Narendra Kumar; Kari Eränen; Anton Tokarev; Markus Peurla; Janne Peltonen; Dmitry Yu. Murzin; Tapio Salmi (My University, 2022)
Five different support materials were modified with 5 wt.% Cu, using an evaporation impregnation method. The synthesized CuCl2/γ-Al2O3, CuCl2/TiO2 (Hombikat), CuCl2/TiO2 (Alfa Aesar), CuCl2/SiO2 and CuCl2/H-Beta-25 materials were characterized by nitrogen physisorption, X-ray powder diffraction, scanning electron microscopy, energy dispersive Xray microanalysis, transmission electron microscopy, Fourier transform infrared spectroscopy and CO2-temperature programmed desorption. The physical-chemical characterization was correlated with catalytic activity, stability and selectivity in the ethylene oxychlorination. It was found that γ-Al2O3 and TiO2 support materials demonstrate very good activity and 1,2dichloroethane selectivity compare to other catalysts. Zeolite H-Beta-25 and SiO2 support materials proved to be unusable for this reaction.